ANALISIS HUBUNGAN LEBAR KATIR TERHADAP STABILITAS DAN KARAKTERISTIK GERAK ROLLING KAPAL PERIKANAN TRADISIONAL PADA SUDUT GELOMBANG BEAM SEA - Moh. Saiful Rahman Hamka; Syafril Mayu Dinata; Santi Febrianti; Aisyah Nur Nabila; Ryzka Arsalia; M. Rakif Panguale; N.A.A. Dinda Agustina (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
Abstract. Outrigger construction is usually used by ships with small sizes that function to increase the stability of the ship. However, the construction of the outrigger has a negative impact on the parking capacity of the ship at the port dock. This study aims to determine the effect of changing the width of the outrigger on the value of ship stability and rolling motion. The research method carried out is by testing ship models with different widths of outriggers. The width variations are 1.75m and 1.25m. Tests were carried out using numerical simulations using ship design software. The parameters analyzed are the ship’s tilt angle (GZ) stability curve area value, maximum tilt angle, and rolling motion response in the form of the Root Mean Square (RMS) value of the ship’s rolling. Based on the results of the study, it shows that changes in the width of the katir can affect the value of ship stability although not too significant, the ship stability value of all model ships is still in accordance with IMO standards or has positive stability. In addition, the rolling RMS value decreases as the width of the outrigger decreases, so the rolling motion of the ship becomes safer for the safety of the fishing boat crew. Ship model 1 has the best stability value than ship model 2 and is closest to the control ship. Ship model 1 has the best rolling RMS value when compared to the rolling RMS value of the control ship and ship model 1.